Technologies of oil, gas and condensate collection and preparation - Burova, M. Y.; Yatskevich, О. О. (National Technical University "Kharkiv Polytechnic Institute", 2026)
The manual contains materials for practical classes in the discipline " Technologies of oil, gas and condensate collection and preparation". The manual provides the basic algorithms for solving the most common tasks. All topics are provided with examples of calculations, accompanied by control questions and tasks for independent work. Intended for students of first (bachelor's) higher education level of the specialty G16 "Mining and oil and gas technologies".
Keywords: teaching guide; natural gas sampling methods; oil; gas; temperature; fire safety; spot sampling